Discovery in Statics - Makarov, Sergey (Scientific research, 2013)
This article described the opening of a new law in fundamental physics, namely the law of the formation of an endless series of suspension (cable-stayed) networks coatings. Opening relates to the mechanics, section of statics
Keywords: Cables; Cable-Stayed Network; Support Contour; Suspension Roof; Space; Space Hotel